Pengaruh Akuntabilitas Pengelolaan Keuangan Desa, Kebijakan Desa, dan Kelembagaan Desa terhadap Kesejahteraan Masyarakat di Desa Tanggan Kecamatan Gesi Kabupaten Sragen - Fanda Vibriyani Sesariya; Setyaningsih Sri Utami (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The purpose of this study was to determine and analyze the effect of village financial management accountability, village policies, and village institutions on community welfare in Tanggan Village, Gesi District, Sragen Regency. Data collection in this study used a questionnaire distributed to respondents. The population in this study was 4,671 people of Tanggan Village using the Slovin formula, so the sample in this study amounted to 368 people of Tanggan Village, Gesi District, Sragen Regency. The type of data used is quantitative data, the data source used is primary data. Data collection techniques using questionnaires through validity and reliability tests. Data analysis techniques using classical assumption tests, namely multicollinearity test, autocorrelation test, heteroscedasticity test, normality test and hypothesis testing using multiple linear regression analysis, t test, F test, coefficient of determination test (R2). The results of this study indicate that the accountability of village financial management has a significant effect on community welfare in Tanggan Village, Gesi District, Sragen Regency. Village policy has a significant effect on community welfare in Tanggan Village, Gesi Subdistrict, Sragen Regency. Village institutions have a significant effect on community welfare in Tanggan Village, Gesi Subdistrict, Sragen Regency.